2021
DOI: 10.53833/puqh8620
|View full text |Cite
|
Sign up to set email alerts
|

‘Moderate’ Islam in Western Counterterrorism Praxes: Countering Extremism or Coercing Negligence?

Abstract: Moderate Islam has been emphasised in Western counterterrorism praxes. In what ways are the Islamic perspective on moderation incorporated into these praxes? To explore this question, the paper adopts decoloniality as its analytical framework and uses an interdisciplinary approach combining Critical Security Studies and Islamic Studies. Relying on critical analyses of secondary counterterrorism discourses and practices as well as key primary Islamic sources, the paper explores the Islamic concept of wasaṭiyya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…At the same time, however, I found two major handicaps on the way to operationalizing an Islamic environmental vision: the persistence of nationalism and intra-Muslim rivalry. I have observed that intra-Muslim conflicts have intensified over the last few decades due to Western counterterrorism discourses and practices (Alkatiri 2018b, Mustapha 2021. Drawing on postcolonial theory and secularization theory, I have analyzed the colonial and domination practices of nation-states in both destroying the environment and marginalizing Muslims on cultural, political, and economic fronts (Alkatiri 2017b(Alkatiri , 2018a(Alkatiri , 2023.…”
Section: Cut the Vicious Circle Let The Muslims Free To Heed The Call...mentioning
confidence: 99%
“…At the same time, however, I found two major handicaps on the way to operationalizing an Islamic environmental vision: the persistence of nationalism and intra-Muslim rivalry. I have observed that intra-Muslim conflicts have intensified over the last few decades due to Western counterterrorism discourses and practices (Alkatiri 2018b, Mustapha 2021. Drawing on postcolonial theory and secularization theory, I have analyzed the colonial and domination practices of nation-states in both destroying the environment and marginalizing Muslims on cultural, political, and economic fronts (Alkatiri 2017b(Alkatiri , 2018a(Alkatiri , 2023.…”
Section: Cut the Vicious Circle Let The Muslims Free To Heed The Call...mentioning
confidence: 99%